The Impact of Product Quality on Brand Switching with Customer Dissatisfaction as a Mediating Factor (A Study on Acer Laptop Users in Ternate City) - Niconoor Taroreh; Abdul Rahman Jannang; Sulfi Abdul Haji (Jurnal Manajemen Sinergi, 2024)
ABSTRACTObjective: This study aims to analyze the effect of product quality on customers' decisions to switch brands, considering the mediating role of customer dissatisfaction.Methodology: This research employs a quantitative approach involving a population of 110 employees from the city of Ternate. The survey was conducted by distributing questionnaires directly using a 5-point Likert scale. Data analysis techniques utilized include Partial Least Square (PLS) with SmartPLS 4.0 software.Findings: The results indicate that the effect of product quality on customer dissatisfaction has a T-statistic value of 2.026 and a P-value of 0.043, indicating a positive and significant influence. Additionally, customer dissatisfaction positively and significantly affects the decision to switch brands. However, the direct effect of product quality on the decision to switch brands is negative and not significant.Conclusion: The results of this research show that: (1) product quality has a negative and insignificant influence on brand switching; (2) product quality has a significant effect on customer dissatisfaction; (3) customer dissatisfaction has a significant effect on brand switching; (4) product quality has a significant effect on brand switching through customer dissatisfaction.